War and health insurance policy in Japan and the United States World War II to postwar reconstruction - Yamagishi, Takakazu 1972- (The Johns Hopkins University Press, 2011)
Those interested in debates about health care in Japan, the United States, and other countries, and especially scholars of comparative political development, will appreciate and learn from Yamagishi's study